2009
DOI: 10.1017/s175173110900398x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bioactive substances on the gastrointestinal tract and performance of weaned piglets: a review

Abstract: The EU ban on in-feed antibiotics has stimulated research on weaning diets as a way of reducing post-weaning gut disorders and growth check in pigs. Many bioactive components have been investigated but only few have shown to be effective. Amongst these, organic acids (OA) have been shown to exert a bactericidal action mediated by non-dissociated OA, by lowering gastric pH, increasing gut and pancreas enzyme secretion and improving gut wall morphology. It has been postulated that they may also enhance non-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 132 publications
0
67
0
2
Order By: Relevance
“…Thymol, the principal constituent of thyme-extract oil, is a phenolic compound with antimicrobial activity. Thymol has been proposed as an animal feed supplement to positively influence gut microbiota and consequently improve animal health and growth (Lallès et al, 2009;Khan et al, 2012). Research has suggested that thymol rapidly enters the bloodstream after it is ingested (Kohlert et al, 2002), and in pigs it is absorbed in the stomach (Michiels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thymol, the principal constituent of thyme-extract oil, is a phenolic compound with antimicrobial activity. Thymol has been proposed as an animal feed supplement to positively influence gut microbiota and consequently improve animal health and growth (Lallès et al, 2009;Khan et al, 2012). Research has suggested that thymol rapidly enters the bloodstream after it is ingested (Kohlert et al, 2002), and in pigs it is absorbed in the stomach (Michiels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, weaning is the most stressful event in piglets' lives, reared in intensive piggeries. Weaning is frequently associated with a reduced nutrient intake, severe growth check, impairment of health status and a higher susceptibility towards infections and gut disorders (14,15) . For more than 50 years, the use of antimicrobial growth promoters (AGP) in animal diets improved growth performance and prevented the side effects of early weaning practice.…”
Section: Introductionmentioning
confidence: 99%
“…Zuren door de voeding of het drinkwater kunnen een positieve bijdrage leveren aan de diergezondheid door hun bactericide werking, het verlagen van de pH van de maag, het stimuleren van de verteringsenzymen en het versterken van de darmintegriteit (Lallès et al, 2009;Partanen and Mroz, 1999).…”
Section: Onderzoekunclassified